Citizens Shaping Complex Technological Issues? Participatory Processes in Bioeconomic and Biotechnological Contexts - Carolin Bohn; Doris Fuchs; Victoria Hasenkamp; Lena Siepker (Politische Vierteljahresschrift, 2023)
In sustainability governance, the reliance on deliberative participatory processes has greatly increased over the last decades due to expectations that such processes can mobilize additional creative potential, foster better understanding of problems and acceptance of the costs of relevant solutions, and mediate the decline in traditional forms of participation. However, in complex technological contexts such as bioeconomics and, especially, biotechnology, participatory processes are still rare, at least partly because of concerns that citizens might lack the necessary information and skills. Yet bioeconomic innovation trajectories often imply societal, political, and economic changes that also affect citizens' lifestyles and budgets and may cohere or conflict with individual and collective norms. Thus, citizen participation in relevant deliberations and decisions would seem opportune. In this paper, we therefore inquire into the potential and challenges for participatory processes in bioeconomic contexts. Specifically, we identify pivotal criteria for the democratic quality of relevant participatory processes on the basis of the rich literature on citizen participation in sustainability governance. We then explore how (well) these criteria can be achieved in participatory processes on the bioeconomy and biotechnological innovation strategies, drawing on two such processes we carried out in 2021 and 2022. On this basis, we propose further questions and implications for research and practice.
Keywords: 320; Participation; Citizens; Bioeconomy; Inclusivity; Empowerment; Partizipation; Bürger; Bioökonomie; Inklusivität